FARMER’S DECISIONS TO TAKE CREDIT IN INDONESIA - Dwi Martha Yulia; Dwi Rachmina; Feryanto Feryanto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Credit is one of the most effective financings at the farmer level because it is more easily accessible to micro-enterprises and is intended to empower farmers to increase their production. However, access to credit at the farmer level is not easy. In addition, the small scale of the farmer's business causes the limited ability of farmers to increase business capital through microfinance institutions and banks. This study aims to analyze factors influencing farmers to take credit in Indonesia. The data analysis method used is binary logit regression which can analyze the relationship between variables that are thought to influence the decision of farmers to take credit using fourteen predictor variables consisting of five demographic variables and nine livestock business variables. The data is sourced from the 2014 Livestock Business Household Survey with a total sample of 42,392 because data that can be used to represent and complete on a national scale for the livestock sub-sector. The results showed that the variables that influenced the decision of farmers to take credit, namely the location of the livestock business, the age of the breeder, gender, type of livestock, number of dependents in the family, farming experience, land ownership, association membership, collective membership, farmer groups, counseling, and partnerships had a significant effect. Statistically. While the variables of education level and ownership of livestock business facilities are not statistically significant. Thus the policy of providing financing and capital facilities through credit distribution as a strategy for empowering farmers and micro business actors in the agricultural sector can be an incentive for farmers to increase their production and can continue to be an instrument of agricultural capital policy.